METHOD OF IMPLEMENTING SDGS IN DAU ALLOCATION IN INDONESIA (CASE STUDY IN THE EASTERN PART OF INDONESIA) - Sukardi; Hamdi (CV. Radja Publika, 2024)
Based on the results of the analysis, it was found that of the three targets, namely the target of increasing water quality, increasing air quality, increasing the quality of land cover, there were three indicators that achieved the target, namely the indicators for the target of increasing water quality, increasing the quality of land cover, with the percentage of performance achieved respectively. by 110.4%; 115.97%; and 100%. In the target indicator of improving air quality, performance achievements were obtained that did not reach the target, with a performance achievement percentage value of 98.85%. This is influenced by the high level of vehicle activity on roads in Denpasar City, the cutting down of trees due to land conversion, and the lack of public awareness in carrying out vehicle maintenance, causing the emissions produced to exceed quality standards. Apart from that, the long dry season in Denpasar City in 2019 also caused the air quality in Denpasar City to decline. During the 2019-2021 period, which remains the largest capital expenditure realization area, the highest average capital expenditure realization was in the cities of Mataram, Kendari and Ambon.